Stand-alone PV system with MPPT function based on fuzzy logic control for remote building applications - Hussain A. Attia; Fernando delAma Gonzalo (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Due to the limitations of reaching the grid utility to remote area, such as rural and/or countryside areas.  Stand-alone photovoltaic power systems represent good alternative that it can be adapted for electrical power delivering to these areas. In this paper, a new design of stand-alone solar system suitable for individual building application is presented. This study focuses on proposing a desired solar PV panels matrix arrangement and connection, in addition to presenting an accurate design of Buck-Boost DC-DC converter which controlled by fuzzy logic controller FLC. The controller guarantees the maximum Power Point working conditions and manipulates the fluctuation of the DC link voltage of the matrix due to the weather changing. The main system includes battery bank charger, single phase inverter, and passive power filter. This study addresses the design and performance analysis the DC side of the 7.85 kW PV system. The system performance is evaluated through MATLAB/Simulink results which reflected the promising indications as an effective system for rural individual stand-alone building applications.